I-Forensics for Halfwith - Fahda Wafiyah Abdul Razak; Nursyaza Nadhirah Ramli; Yahaya Basiron; Mohamad Azani Abd Kadir Jailani; Mohd Hasyir Fadzli; Afiqah Che Endut; Nur Fazidah Asmuje (Kolej PERMATA Insan, 2024)
4th Insan Junior Researchers International Conference 2023 (iJURECON 2023) : "STREAM for a better future”/ editors : Ahmad Fuad Mohamad Amin, Nurhidaya Mohamad Jan, Nur Aisyah Mohamed, Nur Fatin Fathillah Mazlan 27-28 October 2023 Organized by : Kolej Permata Insan